College Students’ Caffeine Intake Habits and Their Perception of Its Effects (Journal of Education and Development, 2019)
Background: Caffeine is a highly used stimulant on college campuses. The prevalence of energy drinks, especially among the younger generations is cause for concern. Purpose: The purpose of this study was to determine the caffeine intake habits of college students and the perception of its effects. Method: The method used was quantitative, cross-sectional, with a descriptive design. The two research questions were: (1) What are the caffeine intake habits of college students? (2) What are the perceptions of the effects of caffeine use among college students? This study was conducted at a college campus in northern Indiana, USA. Participants included 120 male and female students ages 18 years and older. The health belief model was used to guide this study. Results: The study indicated that while caffeine is a commonly used stimulant across campus, overuse was not revealed. Many students reported being able to go 48-72 hours without caffeine and not experiencing withdrawal symptoms when going without it. However, most students do report that they perceive a need to decrease their use of caffeine, as caffeine use has increased since attending college. Conclusion: The review of the literature indicated that the use of caffeine was higher in younger people. However, the research completed as a part of this study from college students indicated that caffeine overuse may not be as prevalent as previously thought.